The mediating role of vaccine hesitancy between maternal engagement with anti- and pro-vaccine social media posts and adolescent HPV-vaccine uptake rates in the US: The perspective of loss aversion in emotion-laden decision circumstances. (August 2021) - Argyris, Young Anna; Kim, Yongsuk; Roscizewski, Alexa; Song, Won
Abstract: While Human Papillomavirus (HPV) is a prominent cause of cervical cancer and mortality among underserved women, HPV vaccine completion rates remain stagnant (54%) among US adolescents. Our objective is to identify how adolescents' mothers' engagement with anti-vaccine versus pro-vaccine social media content is associated with their children's HPV vaccination rates via increased vaccine hesitancy. We employ the notion of loss aversion escalated in an emotion-laden circumstance in consumer behavior literature given that HPV vaccination decisions directly affect children's well-being . Based on this escalated loss aversion tendency for an emotion-laden decision, we explain why anti-vaccine content disproportionately increases mothers' overarching vaccine hesitancy, while pro-vaccine content does not decrease vaccine hesitancy. We conducted a population-based survey among 426 mothers of US adolescents aged 13–18. Our sample closely mimics the socioeconomic and demographic factors of the population group of mothers of adolescents in the US census. Our results show that anti-vaccine social media posts are associated with increases in mothers' overarching vaccine hesitancy and with decreases in their children's HPV vaccination rates, while pro-vaccine content has no significant association with either. Highlights: HPV-associated cancers are a cause of morality, but the vaccination rates are stagnant. We conducted a population-based survey of 426 US mothers of adolescents. Antivaccine posts are associated with increases in mothers' vaccine hesitancy. Antivaccine posts are associated with decreases in adolescents' HPV immunization rates. Vaccine hesitancy mediates the impact of antivaccine posts on HPV immunization rates.